Modelling of pore-blocking behaviors of low-pressure membranes during constant-pressure filtration of an agro-industrial wastewater - Amosa, Mutiu Kolade; Jami, Mohammed Saedi; Al-Khatib, Ma'an Fahmi Rashid; Majozi, Thokozani; Adeniyi, Adewale George; Aderibigbe, Fatai Alade; Abdulkareem, Sulyman Age (CRC Press Taylor & Francis Group, 2019)
Despite the widely documented excellent purification capacity of membranes, their main drawback—fouling—is still being extensively researched with a view to finding a sustainable solution. Fouling simply implies the process that results in the performance loss of a membrane due to the deposition of suspended or dissolved matters onto its external surface or the internal pore walls [1]. Fouling eventually leads to a reduction in the active area of the membrane and thereby results in a reduction in flux below the theoretical capacity of the membrane. Fouling or pore-blocking has been identified as the main reason limiting the adoption of membrane purification processes by many industries. Consequently, an apt understanding of the pore-blocking mechanisms of membranes is imperative, as it is a pertinent factor dictating the overall performance of the filtration process. Pore blockage can occur in any of the two commonly known membrane operations: constant-pressure and constant-flux rate. In a constant-pressure operation, pore blockage usually leads to a sharp decline in permeate flux, while a severe pressure rise is usually encountered in a constant-flux rate operation. In principle, governing filtration models can facilitate the design of membrane processes more than any experiment or characterization can, yet data from experiments are usually required for validation purposes [2–5]. To properly control particulate fouling at the design stage, as well as appropriately monitor it during a plant operation, the methods utilized in evaluating the particulate content of feed-water in predicting membrane fouling are crucial. Soluble and colloidal materials are assumed to be responsible for membrane pore blockage, while suspended solids are mainly accountable for the cake layer resistance [4,6,7]. To accurately measure and predict particulate fouling, it is recommended that specific fouling mechanisms/indices be investigated with respect to specific membranes since the Modified Fouling Index (MFI), where a 0.45 μm membrane filter is used and usually represented as MFI0.45, cannot represent all membrane types. This is due to the fact that some principal parameters such as retention of smaller particulates, the nature and concentration of solutes and solvents, proof of cake filtration, pore size distribution, surface morphology, module hydrodynamics and membrane type/material must be considered in such investigations [1,8]. Therefore, in any proposed membrane process with plans for sustainability, pore-blocking modeling is germane for the determination of some key factors necessary for the design of an efficient membrane system. These factors are: (1) the description of the extent of membrane fouling in terms of particle accumulation at the membrane surface or inside the membrane pores; (2) the prediction of the fouling potential of a specific feed with respect to a specific membrane; and (3) the identification of the most appropriate and sustainable cleaning method necessary for the membrane process. In this study, a systemic investigation was carried out on high-strength agro-industrial wastewater to describe the successive steps involved in the flux decline of a membrane filtration process in terms of pore-blocking mechanism. Microfiltration (MF) and ultrafiltration (UF) membranes, which are the popular low-pressure membranes (LPMs), were utilized for the filtration of the high-strength wastewater. The wastewater is specifically a discharge of an end-of-pipe treatment process from the agro-industry palm oil milling process. An upstream adsorption process was applied to lower the feed strength and reduce its fouling effects on the membranes. The investigative experiments were conducted in a constant-pressure and cross-flow filtration mode through polyethersulfone (PES) MF (pore sizes: 0.1 and 0.2 μm) and UF (molecular weight cut-off: 1, 5 and 10 kDa) membranes at the transmembrane pressures of 40, 80 and 120 kPa. The examined results within the frame of the common blocking mechanisms revealed that the blocking index, η, decreased from 2 to 0 in all five membranes. The pore-blocking phenomenon was successively observed from the complete blocking mechanism (i.e., η = 2) down to the cake filtration mechanism (i.e., η = 0). Furthermore, there is an indication that the early blockage of the pores and formation of a cake resulted in a limiting cake height evident from the near-constant trend of the permeate flux. This means that cake filtration could be best used to explain the fouling mechanisms of the feed on the LPMs based 139Modeling of Pore-Blocking Behaviors of Low-Pressure Membranes on the coefficient of determination (R2) values at all applied pressures. This further demonstrates that the fouling is primarily caused by the gradual reversible cake deposition, which could be easily removed by less onerous cleaning methods.